2008
DOI: 10.1007/s00542-007-0525-8
|View full text |Cite
|
Sign up to set email alerts
|

New horizontal frustum optical waveguide fabrication using UV proximity printing

Abstract: This paper presents a novel method to fabricate the horizontal frustum structure as a planar optical waveguide by using the proximity printing technique. A horizontal frustum optical waveguide with a both lateral and vertical taper structure was produced. The orthogonal and inclined masks with the diffraction effect were employed in lithography process. This method can precisely control each horizontal frustum optical waveguide geometric profile in the fabrication process. The horizontal frustum optical wavegu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Several process parameters impact on the development rate, such as resist thickness, softbake, rehydration, air temperature and humidity, and developer concentration. Previous tests showed that, for the process conditions of table 1, the threshold doses are D 0 = 350 and D 100 = 4500 mJ/cm 2 , for a resist film of 12 µm thick, where D 0 is the minimum absorbed light dose before the resist begin to develop, and D 100 is the maximum dose the resist is The simulation was carried out by using the model presented in previous section (equations [7][8][9]. The optical transmittance of an input image of a dark field line/space mask pattern was generated, as shown in figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several process parameters impact on the development rate, such as resist thickness, softbake, rehydration, air temperature and humidity, and developer concentration. Previous tests showed that, for the process conditions of table 1, the threshold doses are D 0 = 350 and D 100 = 4500 mJ/cm 2 , for a resist film of 12 µm thick, where D 0 is the minimum absorbed light dose before the resist begin to develop, and D 100 is the maximum dose the resist is The simulation was carried out by using the model presented in previous section (equations [7][8][9]. The optical transmittance of an input image of a dark field line/space mask pattern was generated, as shown in figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…The contact exposure of a thick resist works like a proximity printing mode exposure. Many authors have been exploring proximity printing technique, in several fields of MEMS and MOEMS applications (3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the phase transformation caused by the ellipsoid microlens, the diffraction pattern of a laser diode will change from elliptical to circular. The ellipsoid shape of a microlens with variable radii may have the effect of improving the wavefront match between the propagating laser beam and the fiber model [16]. A semiellipsoid microlens can be placed onto the tip of a single-mode fiber end to improve the power coupling efficiency from a laser diode.…”
Section: Discussionmentioning
confidence: 99%
“…An optical fiber has larger dimensions and is circularly symmetrical with a mode radius of about 4.5 μm. The main problems associated with coupling light from an LD into an optical fiber lie in the mismatch between the mode profiles of the laser and the fiber, as well as establishing the alignment between them [1]. The primary challenge for these optical devices results from the extremely stringent submicron alignment tolerance required for high-efficiency coupling.…”
Section: Introductionmentioning
confidence: 99%